Combined effect of Sectional breathing and OM chanting on Motivation and Memory among healthy individuals – A Randomized Controlled Trial - Singh, Sougaijam Khemard; KV, Swathi; P S, Sharada Shetty; Shetty, Vanitha S; Jinaraj, Abhijna (Indian Journal of Integrative Medicine, 2025)
Background and Objectives: Memory is pivotal in daily life, influencing emotional well-being, decision-making, and social interactions. Motivation is crucial in the life of undergraduate college students for improvement in their studies. Yogic practices can help one become calm, a prerequisite for having a good memory and high achievement motivation. Sectional breathing helps the practitioner to achieve more energy and vitality, brings tranquillity to day-to-day activities and reduces stress. ‘OM’ chanting clears the mind of all external distractions, restores focus, and gives the body new energy. Hence, this study aims to assess the combined effect of sectional breathing and OM chanting on motivation and memory in healthy individuals. Materials and Methods: 80 subjects between the age group of 20-28 years were recruited in this randomized controlled trial. Study participants were randomly divided into a study group (Sectional breathing and OM chanting) and a control group (no intervention). PGI Memory Scale (PGIMS) and Deo 0.05– Mohan Achievement Motivation Scale (DMAMS) were assessed before and after the intervention. The results obtained were tabulated and then statistically analysed. Result: Pre- and post-intervention analysis in the experimental group revealed statistically significant differences in DMAMS and PGIMS scores (p ≤ 0.05, respectively). Conversely in the control group, there were no statistically significant differences in both DMAMS and PGIMS scores (p ≥ 0.05). Conclusion: The present study concluded that practice of Sectional breathing and OM chanting for 8 weeks in healthy subjects will bring a positive influence in improving the motivation and memory of the subjects.